Efeito do ácido clorogênico, cafeína e café nas alterações oxidativas e no sistema purinérgico de ratos diabéticos induzidos por estreptozotocina - Stefanello, Naiara (2016)
Studies show that hyperglycemia in diabetes leads to complications in different tissues, mainly caused by the increased production of reactive oxygen species (ROS). The chlorogenic acid is a phenolic compound found in coffee that has antioxidant, neuroprotective and hypoglycemic activity. In addition, caffeine is also found in high concentrations in coffee and it is notable for its antioxidant, neuroprotective and psycho-stimulating action. The objective of this study was to evaluate the effect of chlorogenic acid (ACG), caffeine (CA) and coffee (FC) on hyperglycemia damages in the purinergic system on the cerebral cortex and platelets, as well as evaluate the contribution of the antioxidant defense system facing hyperglycemia in the liver and kidney of diabetes induced by streptozotocin (STZ, 60 mg / kg) in rats. The animals were divided into eight groups: Control; Control/ACG 5 mg/kg; Control/CA 15 mg/kg; Control/CF 0.5 g/kg; Diabetic; Diabetic/ACG 5 mg/kg; Diabetic/CA 15 mg/kg and diabetic/CF 0.5 g/kg. After 30 days of compounds treatment, the animals were euthanized and the cerebral cortex, whole blood, liver and kidney were removed. Our results demonstrated that there was an increase 64.5% and 42% in ATP and ADP concentration, respectively, in diabetic rats when compared to control rats. A increase 173% in ecto-5'-nucleotidase (eN) activity was found in brain cortex synaptosomes of diabetic rats. Treatment with CF promoted an increase 51% in the hydrolysis of ADP by NTPDase in diabetic animals. In platelets, there was an increase in eN and NTPDase activity in diabetic rats when compared to control animals as well as an increase in platelet aggregation in the same group of animals. All treatments decreased the increase in the hydrolysis of these nucleotides in the diabetic groups treated in relation to the diabetic group, but only the treatment with CF and GCA led to a reduction of around 50% and 60%, respectively, in platelet aggregation when compared to untreated diabetic group. We observed an increase in oxidative stress in liver and kidney of untreated diabetic rats according to: reduced activity of SOD (liver 42% and kidney 10.71%), CAT (liver 51.46% and kidney 65, 45%) and vitamin C levels (liver 62.8% and kidney 28.6%) and NPSH (liver 17.5% and kidney 32%) in these animals. It was also observed that liver damage parameters were increased in serum of STZ-treated animals. Of the treatments tested only the ACG treatment showed antioxidant action to restore vitamin C (94.23%) and NPSH (14.6%) levels, as well as to restore catalase activity (116%) in liver of diabetic rats. In turn, CA treatment works by restoring NPSH levels as well as decreasing the increased AST and ALT activity in serum of diabetic rats. CF treatment also reduces the increased activity of AST, ALT and γ-GT enzymes in diabetic rats when compared to untreated diabetic rats. The results showed that these compounds mainly ACG, a compound that presented better effects, can modulate the activity of enzymes of the purinergic system and contribute to the prevention of complications resulting from hyperglycemia and also contribute to the oxidative stress alterations present in diabetes mellitus.